The Effects of IMF Financial Soundness Indicators of Turkish Commercial Banks on the Financial Development Index - Kübra Saka Ilgın (International Journal of Public Finance)
The financial soundness of banks, which are the building blocks of the financial system, is an important indicator that reflects the effectiveness of the financial system. It can be stated that the financial development of countries with an effective financial system will be positively affected by this situation. The paper aims to evaluate the effects of IMF financial soundness indicators of the Turkish commercial banks which have an important share in the Turkish banks, on the financial development index of Türkiye. In this paper, an evaluation was made based on the IMF Financial development index and IMF financial soundness indicators. Panel data analysis was used and panel least squares model estimation was made within the analysis. In line with the findings, it has been determined that sensitivity to profitability, liquidity, and market risks of commercial banks negatively affect financial development while the capital adequacy and asset quality of commercial banks positively affect financial development.